Muhammad Abduh's Thought and Its Practical Implications on Government Work Programs For 2024-2029 - Muhamad Haris; Nurwahidin Nurwahidin; Mulawarman Hannase; Mohammad Izdiyan Muttaqin (Journal of Social Research, 2025)
This research discusses the relevance of the thought of Muhammad Abduh, a reformist Islamic intellectual, to the policies and work programs of the Indonesian government. Muhammad Abduh is known as a figure who championed the reinterpretation of Sharia principles to respond to the challenges of modernity, focusing on social justice, waqf reform, Islamic financial systems, and education. His thinking provides an important foundation for the development of a modern Islamic economy that is inclusive and equitable. In the context of Indonesian government policy, the 2024-2029 work program that carries the vision of Indonesia Emas 2045 integrates the values of Sharia economics and social justice in line with Muhammad Abduh's ideas. Programs such as strengthening the Sharia economy, optimizing ZISWAF (zakat, infaq, sadaqah and waqf) funds, and alleviating extreme poverty reflect the practical implementation of Muhammad Abduh's ideas. The government also emphasizes economic transformation, halal industry development, increasing Sharia financial inclusion, and Islamic values-based education to strengthen global competitiveness. This study uses a descriptive-analytical method to evaluate the relationship between Muhammad Abduh's thought and public policy in Indonesia. The analysis shows that Muhammad Abduh's ideas are not only relevant in addressing national development challenges, but also provide concrete solutions in creating social justice, community empowerment, and strengthening the Sharia economic system. This research also offers practical recommendations on how Muhammad Abduh's Islamic economic principles can be applied more broadly to support sustainable and inclusive development in Indonesia.